2015
DOI: 10.1186/s40064-015-1138-9
|View full text |Cite
|
Sign up to set email alerts
|

Definitive 3D-CRT for clinically localized prostate cancer: modifications of the clinical target volume following a prostate MRI and the clinical benefits

Abstract: PurposeTo evaluate the modifications of the tumor stage and clinical target volume following a prostate magnetic resonance imaging (MRI) to evaluate the tumor (T) staging, and the clinical benefits for prostate cancer.MethodsA total of 410 patients with newly diagnosed and clinically localized prostate cancer were retrospectively analyzed. The patients were treated with definitive three-dimensional conformal radiotherapy (3D-CRT). In all of the patients, digital rectal examination, transrectal ultrasound, pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…This bias was minimised when quantitative parameters such as ADC or semi-quantitative ones such as time-intensity curves were analysed. In addition, this is common clinical practice and is assumed in most published studies on this matter (Panje et al 2015 ; Horsley et al 2015 ; Yamaguchi et al 2015 ; Chang et al 2014 ; Jackson et al 2005 ). Lastly, DRE/TRUS reliability was found to be very low in our study (8.8 %), and this could have influenced the elevated upstaging values observed with mpMRI.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This bias was minimised when quantitative parameters such as ADC or semi-quantitative ones such as time-intensity curves were analysed. In addition, this is common clinical practice and is assumed in most published studies on this matter (Panje et al 2015 ; Horsley et al 2015 ; Yamaguchi et al 2015 ; Chang et al 2014 ; Jackson et al 2005 ). Lastly, DRE/TRUS reliability was found to be very low in our study (8.8 %), and this could have influenced the elevated upstaging values observed with mpMRI.…”
Section: Discussionmentioning
confidence: 94%
“…Such variability can be due to several causes: some studies included patients who underwent MRI after starting HT treatment, leading to a reduction of tumour size and consequently a false downstaging (Panje et al 2015 ; Chang et al 2014 ); on the other hand, most of the studies in this context were performed using 1.5T MRI without endorectal coil (Panje et al 2015 ; Yamaguchi et al 2015 ; Chang et al 2014 ; Jackson et al 2005 ) whereas our investigation was conducted using 3T MRI, with higher diagnostic reliability (Park et al 2007 ). Morphological MRI has been used in most of the reported series without functional associated studies (Horsley et al 2015 ; Yamaguchi et al 2015 ; Chang et al 2014 ; Jackson et al 2005 ). Our study implemented the guide-recommended (Barentsz et al 2012 ) morphological T2 sequences along with two functional studies (DWI and DCE), increasing the diagnosis rate, as previously reported (Wu et al 2012 ; Verma et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation